(untitled) (Minerva, 2019)
It is said that Picasso used the theme of the Rape of Sabine women mainly through the versions given by Poussin and David, and by doing so he changed completely its original meaning into a desperate cry of the weak and humble people against the oppression of the strong ones. In this paper we try to explain the way Picasso went through this changing process.